Sleeping Beauties in Four Epic Works on Library Science by S. R. Ranganathan: An Analytical Study - Bhowmick, Anupam; Santra, Patit Paban; Majhi, Debasis (Journal of Information and Knowledge, 2023)
Dr. S. R. Ranganathan, an Indian librarian and educator who is known as the 'Father of Library Science in India', is also widely known throughout the rest of the world due to his worldwide contribution to library science. Earlier it was difficult to find citations to prominent old research works. New computer technology helps find these types of articles more easily and it also finds sleeping beauties in several disciplines. Here the term 'Sleeping beauty' is used to define a research article life (year) that has been relatively uncited for several years and then suddenly attracts a lot of attention. The present paper describes four sleeping beauties that are found from Ranganathan’s contributions (books only) in library science, such as; Colon Classification (1933), Prolegomena to Library Classification (1937), Philosophy of Library Classification (1951) and Reference Service (1961). Above mentioned four sleeping beauties are detected using three main criteria; depth of sleep, length of sleep, and awakening intensity given by Van Raan (2015) to detect the sleeping beauties.